Nos caminhos da natureza: análise de gêneros na abordagem sistêmico-funcional em livros didáticos de ciências naturais - Silva, Thiago Santos da (2016)
This study aims to map genres used in the teaching of Natural Sciences in the Brazilian school context, more specifically in the 6th year textbooks. Therefore, the research is based on the theoretical and methodological perspective of Systemic Functional Linguistics (SFL), especially in studies related to genre analysis (MARTIN; ROSE, 2008; ROSE; MARTIN, 2012). We adopted as universe of analysis two textbooks offered by the Programa Nacional do Livro Didático (PLND) to Brazilian public schools of basic education in the 2014-2016 triennium (BRASIL, 2013). We selected as corpus chapters of these textbooks that approach three specific contents: living beings nutrition, garbage and macrocosm. The analytical procedures of the corpus followed the principles of Register and Genre Theory (EGGINS; MARTIN, 1997; MARTIN; ROSE, 2008). This analytical approach foresee the grammatical (HALLIDAY; MATTHIESSEN, 2014) and discursive descriptions (MARTIN, 1992; MARTIN; ROSE, 2007) as the basis for identification of record patterns (HALLIDAY, 1989; MARTIN, 1992), which enables check genres used to teach the selected content (VEEL, 1997; COFFIN, 2006; MARTIN; ROSE, 2008; CHRISTIE; DEREWIANKA, 2010). The results in terms of mapped genres were similar to families identified by Veel (1997): procedures, reports, explanations and arguments. Our analysis allowed identifying an unpredicted family by the author, the family of histories. The occurrence of histories in the corpus is due to the Brazilian political-educational context, since the guiding documents of Natural Sciences teaching, such as the Parâmetros Curriculares Nacionais (PCN) (BRASIL, 1998), advise working with contents that allow students to understand the relationships between the current scientific knowledge and its historical evolution. In addition, we also found a genre uncatalogued in previous studies of SFL. We call this genre, which we endorse as part of the family of procedures, procedure for analysis, since its social communicative purpose is request analysis on a given fact/social situation, especially those related to the environmental impact of human actions. The occurrence of this genre is also justified due to political and educational context of Brazil, since the PCN indicate as the goal of teaching Natural Sciences the interpretation of environmental imbalance situations resulting of human interference. Finally, our analysis allowed identifying that genres perform social and communicative purposes not only on the paradigmatic axis (MARTIN; ROSE, 2008), that is, as members of a specific family of genres, but also on the syntagmatic axis, this is, in the way they are combined in the structure of the macro genre book chapter. Our study found that each genre fulfills specific roles in the development of the content in the analyzed chapters. In general, we can ensure that reports and explanations perform the function of expanding the content addressed, the procedures serve to enlarge the content, arguments genres act to take the students to adopt particular placement in relation to the content, and histories serve to historically contextualize the subject studied. In short, although more research of this nature are necessary to strengthen or to reconsider the data we found, these results signal some important aspects of school culture in relation to the Natural Sciences teaching in the Brazilian context, and already show some language characteristics that can be used by language and/or Natural Sciences teachers in reading and writing activities about the phenomena of nature.